THE FLUID OVERLOAD: CAUSES, DIAGNOSIS, COMPLICATIONS, TREATMENT - A. V. Dats; V. I. Gorbachev (Вестник анестезиологии и реаниматологии)
The review describes the current understanding of the fluid overload etiology and the edema propagation mechanisms, as well as the basic metabolic changes which occur under the fluid overload are analyzed. The clinical, laboratory and radiological diagnostic methods and the methods of treatment are given in detail. The international data on the possible complications under the fluid overload are presented.